Cell-free mitochondrial DNA as a pro-inflammatory agent in blood circulation: mechanisms, therapeutic implications, and clinical challenges in immune dysregulation - Zhao, Yangyang; Wu, Chunlei; Liang, Xiaoxue; Yang, Mengjiao (Frontiers in Immunology, 2025)
Circulating cf-mtDNA has emerged as a dual-functional entity in human pathophysiology, serving not only as a disease biomarker but also as a potent innate immune activator through its molecular pattern recognition. Extracellular mtDNA engages PRRs, triggering dysregulated pro-inflammatory signaling in multiple cell lineages. Elevated mtDNA in circulation correlates with pathogenesis of autoimmune disorders, infectious diseases, critical illnesses, neurological disorders, and hematological abnormalities. Therapeutic strategies combining mtDNA monitoring with inhibitors targeting its release mechanisms and downstream pathways offer novel immunomodulatory strategies. This review systematically examines the therapeutic nexus of blood-derived mtDNA in immune activation and disease progression. Here we aim to elucidate the function of mtDNA in disease pathobiology while highlighting mitochondria’s central position in human systemic homeostasis.